Identifikasi Logam Berat dalam Biji Jagung Manis dan Kedelai pada Transisi Sistem Pertanian Organik - Sapto Priyadi; Soelistijono Soelistijono; Setie Harieni; Kusriani Prasetyowati (agriTECH, 2018)
Heavy metal contaminants in land agriculture are environmental problems, and they affect food safety, so there is a need for the research of Pb, Cd and Cu decrease absorption by plants using organic chelating agent, i.e. substance of humus (humic and fulvic acid) in the manure. The research was done with a completely block design, in Gagaksipat, Ngemplak, Boyolali; heavy metal analysis in manure, land and seeds used an atomic absorption spectrophotometer-flame (AAS Jena Contr AA 300, Germany). It was aimed to identify contaminants of Pb, Cd, and Cu in sweet corn and soybean seeds. The research treatments were doses of cow manure: 15, 20, 25, 30, 35, 40, 45 and 50 kg per hectare. The results showed that the enrichment coefficient (EC) of Pb and Cu in sweet corn seeds had low accumulator plants categories; the EC of plumbum in soybean seeds had low accumulator plants categories, whereas the EC of copper soybean seeds had moderate accumulator plants categories; and the EC of cadmium in the sweet corn and soybeans seeds was undetectable. Exposures of Pb and Cd in corn sweet and soybean seeds were undetectable, while exposures of Cu in sweet corn and soybean seeds were 2.03 and 12.39 ppm, respectively. Contamination of Pb, Cd and Cu exposures in land after sweet corn harvested were 30.99; undetectable and 60.58 ppm, respectively. While Pb, Cd and Cu residues in land after soybean harvested were 33.24; undetectable and 56.26 ppm, respectively.